2003
DOI: 10.1002/ijc.11449
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine motility factor signaling induces tumor apoptotic resistance by regulations Apaf‐1 and Caspase‐9 apoptosome expression

Abstract: Autocrine motility factor (AMF) is a cytokine that regulates locomotion and metastasis of tumor cells. It is well known that expression levels of AMF secretion and its receptor (AMF R) are closely related to tumor malignancy and rheumatoid arthritis. We have established that AMF signaling induced anti-apoptotic activity and that human fibrosarcoma HT-1080 line that secreted high levels of AMF were resistant to drug-induced apoptosis. These cells did not express the apoptotic protease activating factor-1 (Apaf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 28 publications
0
68
0
Order By: Relevance
“…30 AMF/PGI activation of pAkt has previously been shown to mediate AMF/PGI anti-apoptosis function. 15,18,25 Indeed, the ability of AMF/PGI to protect against etoposide-induced cell death that is not associated with induction of ER stress, confirms that the anti-apoptotic activity of AMF/PGI is not limited to the ER stress response. Etoposide-induced apoptosis is prevented by inhibition of the PI3K-Akt pathway 31 consistent with previous reports that AMF/PGI protects against serum starvation-induced cell death in NIH-3T3 fibroblasts by PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…30 AMF/PGI activation of pAkt has previously been shown to mediate AMF/PGI anti-apoptosis function. 15,18,25 Indeed, the ability of AMF/PGI to protect against etoposide-induced cell death that is not associated with induction of ER stress, confirms that the anti-apoptotic activity of AMF/PGI is not limited to the ER stress response. Etoposide-induced apoptosis is prevented by inhibition of the PI3K-Akt pathway 31 consistent with previous reports that AMF/PGI protects against serum starvation-induced cell death in NIH-3T3 fibroblasts by PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 82%
“…15,25 The AMF/PGI receptor, gp78/AMFR, is an ER membraneanchored ubiquitin ligase (E3) that is a key component of the ERAD machinery involved in ubiquitination of ER proteins, 26,27 thereby suggesting a possible role in protecting cells against ER stress. In this study, we demonstrate that AMF/PGI protects against ER stress and associated apoptosis by the intermediary of its receptor, gp78/AMFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rAMF Induces Cell Migration but Not Cell Proliferation in Two Melanoma Cell Lines (SBcl-2 and 1205Lu)-AMF is critical for the migration, invasion, metastasis, and anti-apoptotic effects of malignant tumor cells, and its multiple roles in tumor progression may be mediated by certain downstream pathways and effectors (2,5,6,8,(33)(34)(35). A previous study reported that melanoma cells secrete and respond to AMF in an autocrine manner with increased motility (2).…”
Section: Resultsmentioning
confidence: 99%
“…In the formation of metastases, tumor cells first migrate from the primary tumor site to vessels as single cells or masses before entering the circulation which transports them to distant parts of the body. Primary liver cancers are usually treated with pro-apoptotic anti-cancer drugs (Kinoshita et al 2000;Haga et al 2003;Sekharam et al 2003). However, by the time metastases occur, tumor cells have already acquired a resistance to these drugs.…”
Section: Introductionmentioning
confidence: 99%